Peran Budaya Organisasi sebagai Pemoderasi terhadap Motivasi dan Kepemimpinan Transformasional dalam Kinerja Karyawan: Tinjauan Literatur - Hakim, Lukman Huzul (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2024)
This research addresses the lack of understanding regarding the relationship between organizational culture, employee motivation, transformational leadership, and employee performance. A literature analysis of 200 journal articles using the Publish or Perish (PoP) version 8 program shows that a strong and positive organizational culture enhances employee motivation and fosters a work environment that supports innovation and teamwork. Transformational leadership, with its clear vision and emotional support, contributes to the improvement of both individual and group performance. However, further research is needed in various industrial sectors and diverse organizational cultures. In conclusion, the relationship between organizational culture, employee motivation, and transformational leadership have significant effect on employee performance. This implies that managers need to create a positive work environment and effectively implement transformational leadership to boost organizational productivity and success.